Penggunaan Abu Cangkang Karet sebagai Tambahan Filler pada Campuran Aspal Panas Jenis Hot Rolled Sheet - Jojeffrey Etter; Ina Elvina; Robby Robby (Fakultas Teknik, 2022)
A filler is one of the elements or materials that must be present in the hot asphalt mixture. To overcome the lack of filler content, cement or lime is usually used, but in some areas in Indonesia it is sometimes not easy to get cement and the price is relatively more expensive. Therefore, this study tries to examine the effect ofusing rubber shell ash as an additional filler in the asphalt mixture. This study aims to analyze the physical properties, Marshall characteristics, and the optimum value of Rubber Shell Ash using the Asphalt Institute method on a mixture of Lataston Lapis Foundation type HRS-Base (Hot Rolled Sheet -Base). Results Basedon calculations without the addition of rubber shell ash filler, it was found that KAO of 7.35% obtained a Stability value of 900.00 kg, Flow of 3.16 mm, Void in the Mineral Aggregate of 20.7%, Void in the Mix of 4.51%, Void Filled by Bitumen is 77.60%, Marshall Quotient is 285.00 kg/mm. Then it is planned to add 3 variations of Rubber Shell Ash with levels of 1.5%, 3%, and 5%. The best results were obtained with the addition of 5% Rubber Shell Ash with a total filler of 9%, the Stability value was 941.35 kg, Flow was 3.15 mm, the Void in the Mineral Aggregate was 19.70%, the Void in the Mix was 3%, Void Filled by Bitumen was 84, 77%, Marshall Quotient of 300.01 kg/mm.